2022
DOI: 10.1177/21925682221136493
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cervical and Lumbar Decompression Surgery for Spinal Stenosis on Erectile Dysfunction

Abstract: Study design Observational study. Objectives To evaluate the prevalence of erectile dysfunction and evaluate the effects of decompressive surgery on erectile dysfunction in cervical spinal stenosis and lumbar canal stenosis patients. Methods This observational, prospective analysis enrolled patients aged 18-80 with cervical spinal stenosis and/or lumbar canal stenosis that underwent respective decompressive surgery. The IIEF-5 questionnaire was administered preoperatively, and at 6- and 12-months postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They found that patients with lumbar disc disease had lower Female Sexual Function Index (FSFI) scores across all subgroups 9 . Most studies compared sexual function before and after herniated disc surgery, with the prevalence of sexual dysfunction ranging from 26.6 to 80% 1 , 3 , 4 , 9 – 15 . Long-term follow-up indicated poor recovery after surgery 16 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients with lumbar disc disease had lower Female Sexual Function Index (FSFI) scores across all subgroups 9 . Most studies compared sexual function before and after herniated disc surgery, with the prevalence of sexual dysfunction ranging from 26.6 to 80% 1 , 3 , 4 , 9 – 15 . Long-term follow-up indicated poor recovery after surgery 16 .…”
Section: Introductionmentioning
confidence: 99%